Vulval Aggressive Angiomyxoma: A Giant Tumour Arising from Hidradenitis Suppurativa Scars - Sandhya Kumari; Ghanshyam K. Verma; Anchana Gulati; Prajul Mehta (Wolters Kluwer Medknow Publications, 2024)
Aggressive angiomyxoma (AA) is a very rare tumour arising from the vulvovaginal mesenchymal tissue. The literature has not reported its co-existence with hidradenitis suppurativa (HS). A 30-year-old female presented with a giant pedunculated mass arising from a scarred and disfigured perineum for 3 years. On examination, a giant mass of size 20 × 20 cm was hanging over the scarred and disfigured vulva. The clinical possibilities of AA, leiomyoma or angiomyofibroblastoma over the scars of HS were considered. The histopathological examination of the mass revealed the features of AA, and perineal lesion biopsy was suggestive of HS. The patient was managed with surgical excision of the AA along with oral antibiotics for HS.